Antimicrobial action of ozone gas on surfaces and in the air - Caetano, Maicon Henrique [UNESP]; Siqueira, Joao Paulo Zen; Andrade, Denise de; Lopes de Sousa, Alvaro Francisco; Rigotti, Marcelo Alessandro; Diniz, Maiara Oliveira; Almeida, Willian Albuquerque de; Ferreira, Adriano Menis; Gottardo de Almeida, Margarete Teresa (Univ Fed Sao Paulo, Dept Enfermagen, 2021)
Objective: Assess the antimicrobial action of ozone gas (O-3) on surfaces and artificially cooled ambient air. Methods: Cross-sectional experimental/laboratory study carried out in ten rooms of a medical microbiology research lab, with class 2 biosafety risk. The demarcated surfaces on the floor, wall and counter were assessed in relation to the presence or absence of microorganisms, based on collections done with swabs dampened in sterile distilled water, before and after exposure to ozone gas produced by two different generators. After this procedure, each swab was inoculated on the surface of a Brain Heart Infusion Agar DIFCO (R) (BHI) culture, followed by incubation at 35 degrees C for 24 hours. For the microbiological analysis of the air, a petri dish with BHI was openly exposed for one hour, before and after treatment with O-3 gas, and were incubated according to the same criteria. Results: The antimicrobial activity of the O-3 gas produced by both generators was checked in all the areas investigated, with records indicating a decrease in the number of colony-forming units. The antimicrobial inhibition potential of the generators was close to the analysis criteria adopted, particularly for the floor and counter areas. Based on all the rooms and microbial inhibition percentages, in relation to the two generators, the results were: floor (100%), counter (90%), wall (50%) and air (70%). Conclusion: The O-3 generators had antimicrobial potential as a procedure for controlling microorganisms present on surfaces and in artificially cooled ambient air, constituting a feasible sanitizer.
Keywords: Anti-infective agents; Ozone; Ozonation; Disinfection; Products with antimicrobial action; Air pollution; indoor